A comparative study between robotic sleeve gastrectomy and robotic mini gastric bypass: which one is better? - Aggarwal, Ramesh K.; Prasad, Arun; Aggarwal, Kavita (International Surgery Journal, 2023)
Background: Bariatric surgery now days is a commonly done procedure for morbid obese or super obese patients. With the development of less invasive procedures like laparoscopy & robotic surgery, the use of bariatric surgery is becoming more common. The present study was conducted with an idea to compare the post operative outcomes in 2 groups (robotic sleeve gastrectomy & robotic mini gastric bypass) in terms of various parameters such as operative time, post-op. pain, length of hospital stay. Methods: Present study has been conducted on 35 patients, divided into two groups, based on two commonly performed procedures, Group one-21 patients (Robotic one anastomosis gastric bypass/Mini gastric bypass) and group two-14 patients (Robotic Sleeve Gastrectomy). All the cases in both groups were selected according to the patient’s BMI, associated symptoms and patient’s own preference for the procedure; both groups were followed for a period of 6 months. Results: On analysis, group 2 patients had a shorter operating time (p<0.01) and shorter hospital stay (P value<0.05) with almost similar results in term of weight loss after 6 months. Only one patient in group 1 had significant post operative complication in term of pulmonary embolism that was successfully managed conservatively Conclusions: Group 2 had a significantly shorter operating time & shorter hospital stay, with almost similar weight reduction after 6 months period of follow up and had no post operative complication, group 1 had one post operatively complications in term of pulmonary embolism which was managed by conservative means.